A New Therapeutic Era in GCB and ABC Diffuse Large B-cell Lymphom a Molecular Subtypes: A Cell of Origin-Driven Review - D. Sandoval-Sus, Jose; Chavez, Julio; Dalia, Samir (Current Cancer Drug Targets, 2016)
In the past 15 years, advances in molecular biology have exposed the genetic and physiopathologic heterogeneity of diffuse large B-cell lymphoma (DLBCL). Subsets of patients have been identified in which current chemoimmunotherapies may not be as efficacious, such as the activated B-cell subtype (ABC). In this review, we present an in-depth study of the differences between the two main DLBCL subsets (germinal center B cell [GCB] and ABC), focusing specifically on their different genetic features, active tumoral pathways, and pathologic features. We also discuss the bridges that have been built from the bench to the forefront of patient care through translational research, including the use of immunohistochemistry versus gene profiling to categorize patients with DLBCL and current clinical trial data pertaining to new possible targeted therapies for patients with these two subtypes of DLBCL. We hope that clinicians use this review as a tool to better understand the complexity of the two more prevalent DLBCL subtypes seen in the day to day practice and update their knowledge in both current and upcoming novel treatment options that can potentially change the outcomes of this population.
Keywords: treatment